The human milk bacteriome and mycobiome and their inter-kingdom interactions viewed across geography - Sun, Haipeng; Finlay, Brett; Azad, Meghan B.; Cuomo, Christina A.; Cowen, Leah E.; Berdy, Brittany; Livny, Jonathan; Shea, Terrance; Aquino, Edna E.; Godoy-Vitorino, Filipa; Woortman, Melissa A.; Shumaker, Margot; et al. (Frontiers in Nutrition, 2025)
BackgroundThe human milk microbiota is one of the biologically active components of human milk, and factors affecting it and the effect size are not well understood. Assessments of human milk microbiota have mainly been done in small cohorts and/or in single geographical locations, and most have been restricted to the bacteriome. Here we assessed the bacterial, archaeal and fungal composition of human milk and the potential inter-kingdom interactions in milk collected from women living in a wide spectrum of countries, environments, and socio-economical settings.Materials and methodsAbout 518 human milk samples were collected in 16 countries. After DNA extraction, bacterial and fungal metataxonomic analyses were performed via amplification and sequencing of the 16S rDNA and the ITS2 genes, respectively. In parallel, the presence of methanogenic archaea was determined by qPCR.ResultsBacterial analysis revealed significant Country variations in human milk microbiota diversity and taxa distribution. Core genera such as Staphylococcus, Streptococcus, and Bifidobacterium were universally prevalent, and their abundance varied geographically. Methanogenic sequences were found in the amplicon sequences, mostly of Methanobrevibacter (11.8% of samples), while qPCR only detected 0.7% (2 out of 268) methanogens. Fungi—mostly Candida—were detected in 7% of samples, with wide country variations. Co-abundance network analysis revealed mostly positive bacterial correlations and negative inter-kingdom interactions.ConclusionThis study shows substantial global variation in the human milk microbiome with bacterial-fungal interactions, highlighting the importance of global-scale studies to understand the human microbiome and its role in maternal and infant health.